TOP TRADE MARKETING TRENDS IN 2024: INNOVATION AND STRATEGY - Mamatkulova Shoira Djalolovna (Web of Journals Publishing, 2024)
As we enter 2024, trade marketing will continue to grow in response to changing consumer behavior, technological advancements, and market dynamics. In this article, we will primarily look at the trade marketing trends shaping the landscape this year, taking into account the level of innovation and strategic approaches for brands looking to strengthen their presence in the market. Key trends include the integration of data analytics for targeted marketing, the rise of multi-channel strategies, the unification of online and offline experiences, and an increased focus on sustainability and ethical practices in trade marketing efforts. Additionally, advances in digital marketing technologies such as augmented reality (AR) and artificial intelligence (AI) are transforming the way brands interact with consumers in the selling setting. The purpose of this article is to provide insight into these trends, offer actionable strategies for brands to leverage them effectively, and remain sustainable in an ever-evolving competitive market.
Keywords: trade marketing, 2024 trends, innovation, strategy, data analytics, multichannel marketing, sustainability, digital marketing, consumer engagement, augmented reality (AR).